2018
DOI: 10.1111/cdev.13183
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks of Children With Developmental Language Disorder in Inclusive Preschool Programs

Abstract: This study takes an ecological approach to examine how children with developmental language disorder (DLD) interact with their classmates within early childhood special education (ECSE) inclusive classrooms. Participants were 124 children with DLD, 56 children with other disabilities, and 247 typically developing children (Mage = 52.42 months, SD = 6.27) from 56 ECSE inclusive classrooms. Results of social network analysis showed that children with DLD had significantly smaller peer social networks and were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 65 publications
(91 reference statements)
5
28
0
1
Order By: Relevance
“…Comparatively, children, who are insiders of the networks, may perceive their peer interactions beyond the observable cues (e.g., level of trust), which can make their perceptions qualitatively different from the other informants (Pearl et al, 2007;Neal et al, 2011). Another methodological explanation is that the child-report network contains information about the directionality of peer interactions (e.g., who likes to play with a child the most), whereas both the teacher-and the researcher-report networks represented peer interactions between pairs of children without specifying the directionality (i.e., who initiated the interactions) based on the assessment approaches applied in the field (e.g., Martin and Fabes, 2001;Schaefer et al, 2010;Chen et al, 2018;Lin et al, 2019). Unsurprisingly, the level of congruency among child-, teacher-, and researcher-report networks generally decreased as certain binary network transformation approach was applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparatively, children, who are insiders of the networks, may perceive their peer interactions beyond the observable cues (e.g., level of trust), which can make their perceptions qualitatively different from the other informants (Pearl et al, 2007;Neal et al, 2011). Another methodological explanation is that the child-report network contains information about the directionality of peer interactions (e.g., who likes to play with a child the most), whereas both the teacher-and the researcher-report networks represented peer interactions between pairs of children without specifying the directionality (i.e., who initiated the interactions) based on the assessment approaches applied in the field (e.g., Martin and Fabes, 2001;Schaefer et al, 2010;Chen et al, 2018;Lin et al, 2019). Unsurprisingly, the level of congruency among child-, teacher-, and researcher-report networks generally decreased as certain binary network transformation approach was applied.…”
Section: Discussionmentioning
confidence: 99%
“…To test the validity of the three classroom social network measures, we associated these network measures with children’s school records of language ability, social and emotional development, and self-regulation ability, which have been shown in the literature positively related with the amount of play interactions preschoolers engage in classrooms (e.g., Mashburn et al, 2009 ; Justice et al, 2011 ; Ribeiro et al, 2017 ; Chen et al, 2018 ). To account for the small sample size, the 95% confidence intervals (CIs) of correlations coefficients were calculated using a bootstrap approach with 1,000 times of resampling.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study of US preschool children found that 80% showed preferences for same-gender play partners and 50-60% of children's peer interactions were with same gender peers (Martin & Fabes, 2001). Similarly, studies of preschool social networks in the U.S. and European countries consistently demonstrate that social relationships are more likely to exist between same-gender rather than opposite-gender peers (Barbu, 2003;Chen et al, 2019;Chen et al, 2020;Daniel et al, 2013;Daniel et al, 2016;DeLay et al, 2016;Martin et al, 2013;Neal et al, 2017).…”
Section: Preschool Social Network Formationmentioning
confidence: 99%